Chemical quality of bottled mineral waters from markets of Curitiba-PR-Brazil - Santos,Éder José dos (2016)
ABSTRACT Twenty-seven bottled mineral waters from local markets in Curitiba, State of Paraná, Brazil were analyzed for a number of constituents, including: pH, conductivity, total dissolved solids, hardness, HCO3 - and CO 3 2-, as well as Ca2+, Mg2+, Na+, K+, NH4 + , F-, Cl-, NO3 -, NO2 - and SO4 2- by ion chromatography (IC); Al, Ba, Cd, Cr, Cu, Fe, Li, Mn, Ni, Sr, V and Zn by inductively coupled plasma optical emission spectrometry (ICP OES); Hg by cold vapor generation-ICP OES and As, Pb, Sb and Se by ICP-mass spectrometry (ICP-MS). The obtained limits of quantitation (LOQ) were adequate for the determination of all analytes using the various analytical techniques. Results for the analysis of AccuStandard certified reference materials QCS-01-5, QCS-02-R1-5 and TCLP-02-1 as well as spike recoveries to samples show acceptable values, within 90-111 % of expected concentrations with relative standard deviations below 10 %, demonstrating the accuracy of the determinations. Both NO2 - and NO 3 - were above the maximum limits set by Brazilian legislation in two samples, indicating a microbiological contamination. One imported sample presented As (6.1 ± 0.2 µg L-1) near the maximum limit (10 µg L-1) while all other elements of interest were below the values specified by Brazilian legislation. Principal component analysis revealed that four imported samples and one from the Minas Gerais State have the highest mineral concentrations.